Modified Cognitive Behavioral Therapy CBT-FT applied to a case of sexual abuse (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Post-traumatic stress disorder is a serious mental health problem, especially in the most vulnerable population such as children and teenagers. This case study aimed at determining the effects of treatment with Cognitive Behavioral Therapy focused on the Trauma CBT-FT, with the modification in the component of work with the family, in stress levels linked to Post Traumatic Stress Disorder and Depression associated to a case of sexual abuse. The subject is a 14-year-old female served in the Ministry of Public Defense in the City of Encarnación, Paraguay. The experimental design of unique case was used with the modality of multiple baseline, where 4 pretreatment measurements were taken over a month with the Severity Scale Symptoms of Post-Traumatic Stress Disorder and BDI-II. 16 treatment sessions were conducted with weekly measurements and measurements after one month and one-year post treatment. The results showed levels decreased to a minimum on both scales and rates have remained low one year after the intervention. The cognitive restructuring component reported reductions in levels of post-traumatic stress, but not in those of depression significantly, and the component of exposure to rejection showed increases in post-traumatic stress levels, and maintenance of depression levels. The possible explanations and implications of the results are discussed.
Keywords: cognitive behavioral therapy focused on trauma; post-traumatic stress; depression; sexual abuse